Hubungan Pengetahuan Lansia Tentang Pencegahan Hipertensi Dengan Pola Makan Lansia - Siti Mukaromah; Maria Sri Hartati; Siti Maimunah (Jurnal Medika : Karya Ilmiah Kesehatan, 2017)
Elderly is a population group that is the focus of public attention because the elderly are a high risk of degenerative diseases, one of which is hypertension. The wrong diet is one of the risk factors that increase hypertension, the elderly need to increase their knowledge of proper diet for people with hypertension. Aim to find out the relationship of knowledge of the elderly about how to prevent hypertension with an elderly diet at the Poli General Puskesmas Temindung Samarinda. This type of research uses analytical surveys with a Cross Sectional approach. The population in this study were elderly who had hypertension at the General Poly of Temindung Samarinda Health Center with a sample of 47 people determined by accidental sampling technique. The Fisher's Exact Test results obtained a value of ρ (0,000) <α (0.05) indicating that Ha is accepted, which means that there is a relationship between knowledge about prevention of hypertension with an elderly diet at the General Poly of Temindung Samarinda Health Center. Knowledge of the elderly about the prevention of hypertension is related to the diet of the elderly. Therefore, the Puskesmas is expected to be able to improve the diet of the elderly through knowledge about prevention of hypertension so that the health degree of the elderly can be optimal.